Experimental and Numerical Attenuation of Vibration for Delta Wing Using PI Controller - ALi, Ahmed A.; Mahmood, Hussain Y.; Saeed, Mahmood Wael (Al-Nahrain Journal for Engineering Sciences, 2017)
Active vibration controlling loop with proportional - Integral (PI) controller was tested numerically and experimentally for delta wing with three different manufacturing materials; aluminum, [0/90] composite and aluminum foam, both P and PI loop were tested separately. Numerical work was performed in ANSYS v.15 where controller with piezoelectric transducers was totally integrated in program macro. Experimental wings where fabricated to be tested under simulated excitation. Labview 2015 program with high speed Data acquisition were used besides actuators to perform controlling circuit experimentally. Good suppression in wing oscillation was performed where 72% of wing’s time of vibration was eliminated for aluminum foam wing. Noticeable agreement was achieved between experimental and numerical responses.